A metal mesh, electrode material and battery

CN224708776UActive Publication Date: 2026-09-01SHANGHAI ZHONGDINGSHENG HIGH-TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202521601528.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-07-29
Publication Date
2026-09-01
Estimated Expiration
2035-07-29

AI Technical Summary

Technical Problem

但这种制备工艺复杂,且获得的多孔电极材料的机械性能差,容易碎裂

Benefits of technology

[0021]采用上述技术方案,电极材料通过采用具有蜂窝状网络结构的金属网,不仅显著提高了电极材料的比表面积、离子传输效率和能量密度,还优化了电极材料的稳定性和机械性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224708776U_ABST
    Figure CN224708776U_ABST
Patent Text Reader

Abstract

This invention discloses a metal mesh, which serves as an electrode active material or electrode substrate in a battery. The metal mesh is a honeycomb-like grid structure formed by stacking, fixing, and stretching multiple layers of rolled metal foil with a thickness of 0.01 μm to 100 μm in a first direction. The mesh openings are through holes, formed by the spacing between adjacent rolled metal foils through stretching. This invention also discloses an electrode material and a battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This utility model relates to the field of batteries, and in particular to a metal mesh, electrode material, and battery used in batteries. Background Technology

[0002] As a core means of energy storage and conversion, the performance of batteries plays a crucial role in the application and development of various electronic devices, new energy vehicles, and renewable energy systems. The internal electrode structure of a battery significantly impacts its performance; in particular, the performance of the electrode active materials and the electrode substrate are key factors influencing the electrode structure. "Electrode active materials" typically refer to the materials in the battery that directly participate in the electrochemical reaction and release electrical energy. "Electrode substrate" refers to the conductive framework or current collector that supports the electrode active materials; its main functions are to provide mechanical support and electronic conduction pathways for the electrode active materials, and to ensure sufficient contact between the electrode active materials and the electrolyte.

[0003] Currently, the electrode substrates and electrode active materials widely used in the market have many shortcomings. Traditional electrode substrates mostly use metal foils (such as copper foil and aluminum foil), but this structure cannot fully meet the battery performance requirements due to the limited contact area with the electrolyte.

[0004] To address these issues, existing technologies have proposed porous structures as an improvement. However, porous structures still present numerous challenges in practical applications and production. For instance, foamed metals (such as foamed copper and foamed aluminum) are typically produced through powder metallurgy or electroplating. Powder metallurgy involves adding a foaming agent to powder, which volatilizes during sintering, leaving pores. Electroplating involves electrochemically depositing metal onto a porous organic matrix, followed by sintering to remove the organic matrix. While these methods increase the specific surface area in contact with the electrolyte to some extent, the uniformity and tortuosity of the pore structure are often difficult to control precisely, limiting electrolyte permeability and ion transport efficiency. Furthermore, the processes for producing foamed metals through powder metallurgy or electroplating are complex and costly, hindering large-scale, efficient production.

[0005] Existing technologies also propose fabricating porous metals through electrochemical, photolithography, or laser cutting of metal foils. However, photolithography and laser cutting processes struggle to guarantee pore size uniformity, especially in large-area fabrication, where pore size can vary significantly due to processing errors. Furthermore, during photolithography and laser cutting, burrs or cracks can form at the pore edges due to etching or high temperatures, increasing surface roughness and reducing conductivity. In addition, photolithography and laser cutting typically require layer-by-layer or point-by-point processing, resulting in low production efficiency.

[0006] Electrode active materials are typically mixed with conductive agents and binders in powder form before being coated onto current collectors to form electrode materials. This makes the powdered electrode active material prone to detachment during charge and discharge due to volume expansion and contraction, leading to decreased electrode material stability. To address this, existing technologies involve mixing the powdered electrode active material with conductive agents and binders, coating and depositing the mixture onto a porous organic substrate, and then sintering to remove the organic substrate to obtain a porous structure as the electrode material. However, this preparation process is complex, and the resulting porous electrode material has poor mechanical properties and is easily fractured. Furthermore, both methods require the use of conductive agents and binders. While the addition of these agents can improve the conductivity and adhesion of the electrode active material, it also increases the internal resistance of the electrode material, reducing the battery's energy density and charge / discharge efficiency. Utility Model Content

[0007] To solve the above-mentioned technical problems, the embodiments of this utility model provide a metal mesh, an electrode material, and a battery.

[0008] In a first aspect, the present invention discloses a metal mesh, which serves as an electrode active material or electrode substrate in a battery. The metal mesh is a honeycomb-shaped grid structure formed by stacking, fixing and connecting and stretching multiple layers of rolled metal foil with a thickness of 0.01μm to 100μm in a first direction. The mesh openings of the metal mesh are through holes, and the mesh openings are formed by the spacing between adjacent rolled metal foils through stretching.

[0009] Using the above technical solution, the metal mesh, as an electrode active material or electrode substrate in the battery, has a honeycomb mesh structure, through holes, pore walls made of rolled foil, and ultra-thin pore wall thickness. This not only helps to improve the electrical properties of the electrode material, including conductivity, ion transport performance, interfacial resistance, and energy density, but also helps to enhance the mechanical properties of the electrode active material or electrode substrate, such as tensile strength and elongation.

[0010] Secondly, embodiments of this utility model disclose a metal mesh, which serves as an electrode active material or electrode substrate in a battery. The mesh has through holes, and the holes are arranged to form a honeycomb-like grid structure. The holes are formed by the spacing between adjacent rolled metal foils in a multilayer stacked rolled metal foil, wherein the hole walls between adjacent holes are the base layer of the rolled metal foil, and the thickness of the hole walls is 0.01 μm to 100 μm.

[0011] By adopting the above technical solution, the metal mesh can be used as an electrode active material or electrode substrate in the battery. Its honeycomb mesh structure, through holes, pore walls made of rolled foil, and ultra-thin pore wall thickness not only optimize electrolyte permeation and ion transport efficiency and improve the electrical performance of the electrode active material or electrode substrate, but also enhance the mechanical properties of the electrode active material or electrode substrate and extend the cycle life of the battery.

[0012] According to another specific embodiment of this utility model, the specific surface area of ​​the metal mesh is 0.1 m². 2 / g~100m 2 / g.

[0013] According to another specific embodiment of the present invention, the rolled metal foil is copper foil, aluminum foil, lithium foil, steel foil, iron foil, or nickel foil.

[0014] According to another specific embodiment of this utility model, when the rolled metal foil is copper foil, the tensile strength of the rolled metal foil is 200-350 MPa; when the rolled metal foil is aluminum foil, the tensile strength of the rolled metal foil is 120-200 MPa; when the rolled metal foil is steel foil, iron foil, or nickel foil, the tensile strength of the rolled metal foil is 400-700 MPa; and when the rolled metal foil is lithium foil, the tensile strength of the rolled metal foil is 30-100 MPa.

[0015] According to another specific embodiment of the present invention, the surface roughness (Rz) of the rolled metal foil is 0.6 to 1.5 μm.

[0016] According to another specific embodiment of the present invention, the cross-sectional shape of the mesh is quadrilateral or hexagonal.

[0017] According to another specific embodiment of the present invention, the thickness of the hole wall between adjacent mesh holes is 0.01μm to 100μm.

[0018] According to another specific embodiment of the present invention, the volume of the plurality of mesh openings accounts for 75% to 99.994% of the volume of the metal mesh.

[0019] According to another specific embodiment of the present invention, the thickness of the metal mesh is 0.1mm to 50mm.

[0020] Thirdly, embodiments of this utility model disclose an electrode material, including a metal mesh as described in either the first or second aspect.

[0021] By employing the above technical solution, the electrode material, through the use of a metal mesh with a honeycomb network structure, not only significantly improves the specific surface area, ion transport efficiency, and energy density of the electrode material, but also optimizes the stability and mechanical properties of the electrode material.

[0022] Fourthly, embodiments of this utility model also disclose a battery, including the electrode material as described in the third aspect embodiment.

[0023] By adopting the above technical solution, the battery of this utility model, through the use of the above electrode material, which has a honeycomb network structure, significantly improves the battery's ion transport efficiency, energy density, cycle stability, and safety. Attached Figure Description

[0024] Figure 1 This shows a scanning electron microscope image of the metal mesh in a specific embodiment of the present invention;

[0025] Figure 2 A three-dimensional schematic diagram of the metal mesh in a specific embodiment of this utility model is shown;

[0026] Figure 3 This diagram shows a three-dimensional schematic of the stacked layers in a specific embodiment of the present invention.

[0027] Figure 4 A top view of the metal mesh in a specific embodiment of this utility model is shown;

[0028] Figure 5 A metallographic image of the surface of a rolled copper foil is shown.

[0029] Figure 6 A metallographic image of the surface of the electrolytic metal foil, which is copper foil, is shown.

[0030] Figure 7 A photograph showing the structural form of the stacked layers formed by artificial stretching in a specific embodiment of this utility model;

[0031] Figure 8 A photograph of the metal mesh of Embodiment 2 of this utility model is shown;

[0032] Figure 9 Photograph 2 shows the metal mesh of Embodiment 2 of this utility model.

[0033] (Symbol Explanation)

[0034] x. First direction, y. Thickness direction, d1. Hole wall thickness, d2. Metal mesh thickness, 1. Rolled metal foil, 10. Mesh opening, 11. Contact area. Detailed Implementation

[0035] The following specific embodiments illustrate the implementation of this utility model. Those skilled in the art can easily understand other advantages and effects of this utility model from the content disclosed in this specification. Although the description of this utility model will be presented in conjunction with preferred embodiments, this does not mean that the features of this utility model are limited to this embodiment. On the contrary, the purpose of describing the utility model in conjunction with the embodiments is to cover other options or modifications that may be derived based on the claims of this utility model. To provide a deep understanding of this utility model, many specific details will be included in the following description. This utility model may also be implemented without using these details. Furthermore, to avoid confusion or obscuring the focus of this utility model, some specific details will be omitted in the description. It should be noted that, without conflict, the embodiments and features in the embodiments of this utility model can be combined with each other.

[0036] It should be noted that in this specification, similar reference numerals and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.

[0037] The terms “first”, “second”, etc., are used only to distinguish descriptions and should not be interpreted as indicating or implying relative importance.

[0038] In the description of this embodiment, it should also be noted that, unless otherwise explicitly specified and limited, the terms "set up," "connected," and "linked" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this embodiment based on the specific circumstances.

[0039] To make the objectives, technical solutions, and advantages of this utility model clearer, the embodiments of this utility model will be described in further detail below with reference to the accompanying drawings.

[0040] Firstly, such as Figures 1-4 As shown, an embodiment of this utility model discloses a metal mesh, which serves as an electrode active material or electrode substrate in a battery. The metal mesh is composed of multiple layers of rolled metal foil 1 in a first direction (e.g., Figures 2-4 Stacked in the x-direction shown, adjacent rolled metal foils 1 are fixedly connected in the first direction, and then along the first direction (e.g., in the x-direction). Figures 2-4 The multilayer rolled metal foil 1 is stretched in the x-direction shown to form a honeycomb mesh structure, wherein the mesh openings 10 are along the thickness direction of the metal mesh (e.g., along the x-direction). Figure 2 and Figure 3The through-hole extends and penetrates in the y-direction (as shown). The mesh 10 is formed by spacing adjacent rolled metal foils 1 through stretching. The thickness of the rolled metal foil 1 is 0.01 μm to 100 μm. For example, the thickness of the rolled metal foil 1 is 0.01 μm to 10 μm. For example, the thickness of the rolled metal foil 1 is 0.01 μm, 0.05 μm, 1 μm, or 10 μm.

[0041] Specifically, the surface of the rolled metal foil 1 is provided with uniformly spaced contact areas 11, and the multilayer rolled metal foil 1 is arranged along a first direction (e.g., Figures 2-4 After stacking (as shown in the x-direction), adjacent rolled metal foils 1 are fixedly connected through contact areas 11 to form a stack. Then, along the first direction (e.g., in the x-direction), Figures 2-4 The stretching and stacking in the x-direction (as shown) creates gaps between adjacent rolled metal foils 1, forming mesh openings 10. That is, the walls of the mesh openings 10 between adjacent openings 10 are formed by the layered matrix of the rolled metal foils 1; specifically, the opening walls are the unfixed areas on the layered matrix of the rolled metal foils 1. These unfixed areas are other areas (i.e., non-contact areas) relative to the contact area 11, and can also be called free areas. The thickness of the unfixed areas is the thickness d1 (i.e., wall thickness) of the opening walls. In other words, the free areas of adjacent rolled metal foils 1 are stretched during the stretching process to form mesh openings 10, which are uniformly and regularly distributed along a plane perpendicular to the thickness direction of the metal mesh. This plane is also the extension plane of the metal mesh. The mesh openings 10 are located along the thickness direction of the metal mesh (e.g., along the thickness direction of the metal mesh). Figure 2 and Figure 3 Extending in the y-direction shown, wherein the thickness direction (e.g.) Figure 2 and Figure 3 The y-direction shown is perpendicular to the first direction (e.g., the direction shown in the image). Figures 2-4 (shown in the x-direction).

[0042] This utility model relates to a metal mesh formed by stacking, fixing, and stretching multiple layers of rolled metal foil 1, which can efficiently obtain a honeycomb mesh structure with uniform pore distribution. The formed honeycomb mesh structure can evenly distribute stress in all directions, effectively buffering the volume changes (expansion / contraction) of the metal mesh during charging and discharging, avoiding damage to the electrode structure, and thus extending the cycle life of the battery.

[0043] In this specific embodiment of the invention, the metal mesh is formed by stacking, fixing, and stretching rolled metal foil 1. Rolled metal foil refers to a metal foil with a thickness (e.g., about 20 cm) relatively large compared to a metal raw material (e.g., a metal ingot or block), which is then repeatedly rolled and annealed to form a metal foil with the required thickness. The metal raw material is a non-electrolytic metal. The rolled metal foil of this invention differs from electrolytic metal foil, which is obtained by depositing a uniform film of the desired metal onto a bright stainless steel (or titanium) roller using an electroplating solution containing the desired metal, followed by continuous peeling and winding.

[0044] The rolled metal foil 1, after repeated rolling, exhibits high density and low surface roughness. This invention utilizes an extremely thin rolled metal foil to form a metal mesh. Compared to extremely thin metal foils obtained through electrolysis, deposition, or other methods, the rolled metal foil used in this invention has higher mechanical strength and a smoother, flatter surface. The resulting metal mesh, as an active material or metal substrate, is more conducive to improving battery electrical performance. The rolled metal foil is also less prone to damage when stretched to form a honeycomb mesh structure. Furthermore, the rolling process is more efficient and suitable for large-scale production.

[0045] like Figure 5 and Figure 6 As shown, compared to electrolytic metal foil, rolled metal foil 1 has a smaller surface roughness, which shortens the transport distance of ions and electrons on the electrode substrate surface or the electrode active material surface. The high density of rolled metal foil 1 indicates higher tensile strength and elongation, further improving the mechanical properties of the metal mesh. This application uses rolled metal foil with a thickness of 0.01 μm to 100 μm, meaning the thickness d1 of the hole wall between adjacent mesh openings 10 is 0.01 μm to 100 μm. Studies have shown that such a thickness of rolled metal foil 1 gives the honeycomb mesh structure of this invention a larger specific surface area. A larger specific surface area means more active sites, which can significantly improve the energy density of the battery.

[0046] Compared to foamed metals (such as foamed copper), the metal mesh of this invention not only has a honeycomb network structure, but its mesh openings 10 are also independent and interconnected through-holes extending along the thickness direction. This provides a rapid and uniform permeation channel for the electrolyte, allowing it to quickly and evenly reach every corner of the electrode material, accelerating the ion transport process. This highly efficient electrolyte permeation and ion transport capability can effectively shorten the battery's charge and discharge time, increase the battery's power density, and make the metal mesh of this invention more suitable for high-power applications, such as fast charging of electric vehicles.

[0047] Porous metals prepared by photolithography or laser cutting of layered metal foils have pore walls composed of the remaining layered metal foil after photolithography or laser cutting. These pore walls are relatively thick, and thin pore walls are difficult to control. Furthermore, the pore walls prepared by the aforementioned perforation methods have inherently weak smoothness and mechanical properties. Additionally, existing active materials formed by perforation, such as porous lithium, and current collectors, such as porous copper foil and porous aluminum foil, form two-dimensional layered materials. To increase specific surface area and electrical performance, the strategy employed is to reduce the thickness of these two-dimensional layered materials. In contrast, the metal mesh of this application is a three-dimensional structure formed by stacking, fixing, and stretching multiple layers of rolled metal foil 1. Its mesh openings are formed by the unfixed areas of adjacent rolled metal foil 1. The rolled metal foil 1 constituting the mesh pore walls is formed through a rolling process, requiring a thickness of 0.01 μm to 100 μm. This results in a relatively thin thickness for the rolled metal foil 1, which, when rolled to this thickness, exhibits high density and low surface roughness. Consequently, the pore walls between the mesh openings 10 in the resulting metal mesh possess the properties of the rolled metal foil 1. This translates to an increased specific surface area of ​​the metal mesh, a reduced current density per unit area, and effective prevention of phenomena such as lithium dendrite formation. Furthermore, the pore walls are more robust, thereby improving the electrical and mechanical properties of the electrode material.

[0048] Furthermore, when the metal mesh of this invention is used as the electrode active material in a battery, its three-dimensional structure allows it to be used directly as the electrode material, eliminating the need for adding conductive agents and binders in traditional electrode material preparation processes, and eliminating the need for additional current collectors for support. This allows the electrode active material of this invention to not only fully contact the electrolyte, improving the conductivity of the electrode material, but also avoids the problems of increased internal resistance and reduced energy density caused by the addition of conductive agents and binders. It also simplifies the electrode material preparation process and reduces production costs.

[0049] Therefore, by adopting the above technical solution, the metal mesh of this utility model has a honeycomb network structure, with mesh openings 10 being through holes and the thickness d1 of the mesh wall being 0.01μm to 100μm. This metal mesh, as an electrode active material or electrode substrate in a battery, not only improves the electrical properties of the electrode material, including conductivity, ion transport performance, interfacial resistance, and energy density; it also enhances the mechanical properties of the electrode material, such as tensile strength; and facilitates electrolyte permeation.

[0050] Secondly, such as Figures 1-4 As shown, this utility model provides a metal mesh, which serves as an electrode active material or electrode substrate in a battery. The mesh openings 10 of the metal mesh are arranged along the thickness direction (e.g., ...). Figure 2 and Figure 3The through holes (shown in the y direction) extend in a honeycomb grid structure. The mesh 10 is formed by the gaps between adjacent rolled metal foils 1 in the multi-layer stacked rolled metal foil 1. The hole wall between adjacent mesh 10 is the base layer of the rolled metal foil 1. The thickness d1 of the hole wall is 0.01μm to 100μm.

[0051] In this design, the substrate layer of the rolled metal foil 1 is the unfixed area of ​​the rolled metal foil. The unfixed area refers to other areas relative to the contact area (i.e., non-contact areas), and can also be called the free area. In this case, the thickness of the unfixed area is the thickness d1 of the hole wall. In other words, the free areas of adjacent rolled metal foils 1 are stretched during the stretching process to form a mesh 10, which is parallel to a first direction (e.g., ...). Figures 2-4 The planar distribution is regular (as shown in the x-direction), and along the thickness direction of the metal mesh (e.g., Figure 2 and Figure 3 (Extends in the y-direction shown).

[0052] Using the metal mesh as the electrode active material or electrode substrate in the above technical solution, its honeycomb mesh structure, through-holes, pore walls formed by rolled metal foil, and ultra-thin pore wall thickness not only improve the electrical performance of the electrode material but also enhance its mechanical properties and optimize electrolyte permeation, thereby ensuring the overall performance of the battery. This overall performance includes energy density, initial charge-discharge efficiency, cycle life, thermal stability, and mechanical properties. Specific details are as described above and will not be repeated here.

[0053] In some possible embodiments provided by this utility model, an electrode active material is disclosed, which is a metal mesh as described above. Specifically, the electrode active material can be a negative electrode active material, more specifically a lithium negative electrode material, such as a honeycomb lithium electrode.

[0054] In some possible embodiments provided by this utility model, an electrode substrate is disclosed, which is a metal mesh as described above. Specifically, the electrode substrate can be a current collector, such as honeycomb copper foil or honeycomb aluminum foil.

[0055] In some possible embodiments provided by this utility model, the rolled metal foil 1 is copper foil, aluminum foil, lithium foil, steel foil, iron foil, or nickel foil. When the rolled metal foil 1 is steel foil, copper foil, or aluminum foil, the metal mesh serves as the electrode substrate in the battery; when the rolled metal foil 1 is lithium foil, steel foil, iron foil, or nickel foil, the metal mesh serves as the electrode active material in the battery.

[0056] In some possible embodiments provided by this utility model, the rolled metal foil 1 is in a hard state or a soft state. Preferably, the rolled metal foil 1 is in a hard state. In this embodiment, the hard rolled metal foil can be understood as a rolled metal foil with high tensile strength. For example, when the rolled metal foil 1 is copper foil, the tensile strength of the hard rolled metal foil 1 is 200-350 MPa; when the rolled metal foil 1 is aluminum foil, the tensile strength of the hard rolled metal foil 1 is 120-200 MPa; when the rolled metal foil 1 is steel foil, iron foil, or nickel foil, the tensile strength of the hard rolled metal foil 1 is 400-700 MPa; when the rolled metal foil 1 is lithium foil, the tensile strength of the hard rolled metal foil 1 is 30-100 MPa. In other words, the hard metal used in the rolled metal foil 1 in this embodiment of the present invention enables the mesh walls to have high hardness and tensile strength, thereby enabling the metal mesh of the present invention to withstand greater mechanical stress, which helps to improve the mechanical properties of the electrode material.

[0057] In some possible embodiments provided by this utility model, the surface roughness (Rz) of the rolled metal foil 1 is 0.6–1.5 μm. The surface roughness (Rz) of the electrolytic metal foil is generally 4 μm or more. Therefore, compared to electrolytic metal foil, the transport distance of ions and electrons on the metal mesh can be effectively shortened. Furthermore, when the metal mesh is the electrode substrate, such a range of surface roughness allows the electrode substrate to have suitable adhesion, thereby enabling the active material to adhere more firmly to the electrode substrate, reducing the shedding of the active material during charging and discharging, and thus improving the stability of the electrode and the cycle life of the battery.

[0058] Furthermore, in this embodiment, the cross-sectional shape of the mesh 10 is polygonal, and more specifically, hexagonal or quadrilateral. For example, the cross-sectional shape of the mesh 10 is hexagonal. The hexagonal structure has excellent structural stability, making the mesh walls less prone to local collapse, better maintaining the original pore structure of the metal mesh, and ensuring stable mechanical and electrical properties. In addition, the hexagonal mesh can provide the maximum porosity and specific surface area per unit volume. This means that, under the same volume or mass, the hexagonal mesh 10 can accommodate more active material or provide more active sites, thereby significantly improving battery capacity. For example, the cross-sectional shape of the mesh 10 is quadrilateral. This means that when adjacent rolled metal foils are fixedly connected through a contact area, this contact area can be, for example, dot-shaped or line-shaped, which is beneficial for further increasing the specific surface area of ​​the metal mesh. Furthermore, the quadrilateral is rhomboid, that is, the cross-sectional shape of the mesh 10 is rhomboid. The symmetrical rhomboid structure also helps to ensure stable mechanical and electrical properties of the metal mesh.

[0059] In some possible embodiments provided by this utility model, the thickness d1 of the hole wall between adjacent mesh openings is 0.01 μm to 12 μm, that is, the thickness of the rolled metal foil 1 used in the specific embodiment of this utility model is 0.01 μm to 12 μm. At this thickness, on the one hand, the specific surface area of ​​the metal mesh can be significantly increased, thereby improving the conductivity of the electrode material and the energy density of the battery. On the other hand, the thinner wall thickness also means that electrons and ions need to travel a shorter path during transport, thereby reducing the internal resistance of the metal mesh, which is beneficial to achieving higher energy density and longer battery life.

[0060] Furthermore, the thickness d1 of the pore wall between adjacent mesh openings is 0.01 μm to 6 μm, meaning the thickness of the rolled metal foil 1 is 0.01 μm to 6 μm. According to existing industry standards, metal foils with a thickness ≤12 μm are called ultra-thin metal foils, and those with a thickness ≤6 μm are called extremely thin metal foils. Currently, existing electrolytic metal foils can reach the level of extremely thin metal foils. The rolled metal foil 1 used in this invention achieves the thickness level of electrolytic metal foils, further increasing the specific surface area of ​​the metal mesh. This means that, under the same volume or mass, the metal mesh can provide more active sites, greatly promoting the contact and reaction between the electrode and the electrolyte. During battery charging and discharging, this will significantly accelerate ion transport, further shorten charging and discharging time, and also help to further reduce the internal resistance of the electrode material and improve the energy density of the battery.

[0061] Furthermore, the thickness d1 of the wall between adjacent mesh openings is 0.01 μm to 1 μm. The applicant was surprised to find that when using rolled metal foil 1 with a thickness of 0.01 μm to 1 μm, the resulting metal mesh can possess a very high specific surface area. Taking rolled copper foil as an example, the specific surface area of ​​the obtained copper metal mesh can reach 0.22 m². 2 / g~22.4m 2 / g. Accordingly, when used as an active material or current collector, it can maintain extremely low internal resistance, thereby greatly improving the conductivity of the electrode material and the energy density of the battery.

[0062] In some possible embodiments provided by this utility model, the volume of the multiple mesh openings 10 accounts for 75% to 99.994% of the volume of the metal mesh, which can be understood as the porosity of the metal mesh being 75% to 99.994%. This means that the effective surface area of ​​the metal mesh in contact with the electrolyte is significantly increased. This directly promotes the ion transport rate between the electrode active material and the electrolyte, allowing active materials such as lithium ions to be inserted and extracted more quickly and uniformly within the metal mesh, thereby significantly improving the rate performance of the battery. That is, the battery's charge and discharge capability at high current densities is significantly enhanced, polarization is reduced, and the charge and discharge time is shortened. Furthermore, when the metal mesh is the electrode substrate, such a porosity range also means that more active material can be accommodated in the same volume or mass, thereby significantly improving the energy density of the battery. Specifically, the cross-sectional area of ​​a single mesh opening 10 is 1.50 × 10⁻⁶. -6 ~3.50×10 -6 m 2 For example, the cross-sectional area of ​​a single mesh 10 is 2.60 × 10⁻⁶. -6 m 2 The volume of a single mesh 10 is 0.01–0.05 m³. 3 For example, the volume of a single mesh 10 is 0.03m³. 3 .

[0063] In some possible embodiments provided by this utility model, the thickness d2 of the metal mesh is 0.1mm to 50mm. A metal mesh of this thickness is beneficial for improving the rate performance of the battery, i.e., its rapid charge and discharge capability, and also helps to reduce concentration polarization. Furthermore, a metal mesh of this thickness can accommodate more active material per unit area, which helps to improve the energy density of the electrode material and even the entire battery. By controlling the thickness d2 of the metal mesh to 0.1mm to 50mm, a good balance can be achieved between mechanical strength, ion transport efficiency, and energy density, avoiding problems such as insufficient capacity due to excessively thin electrodes or mass transfer obstruction and increased polarization due to excessively thick electrodes. For example, the thickness d2 of the metal mesh is 0.1mm to 0.5mm or 0.5mm to 50mm.

[0064] In any of the above embodiments, the specific surface area of ​​the metal mesh is 0.1 m². 2 / g~100m 2 / g, specifically, the specific surface area of ​​the metal mesh is 0.1m². 2 / g~5m 2 / g、5m 2 / g~10m 2 / g, 10m 2 / g~25m 2 / g、25m 2 / g~50m 2 / g, 50m 2 / g~75m 2 / g or 75m 2 / g~100m 2 / g. Studies have found that such a specific surface area not only provides sufficient active sites for electrochemical reactions, improves the stability of electrode materials, and increases the energy density of the battery, but also avoids the occurrence of side reactions caused by excessively high specific surface area.

[0065] Specifically, during battery charging and discharging, ions need to be inserted and extracted onto the surface of the electrode material. A larger specific surface area provides more active sites for ion reactions, thus accelerating ion transport, shortening charge and discharge time, and increasing power density. However, too many active sites can lead to unnecessary reduction or oxidation reactions in the electrolyte on the electrode surface, generating byproducts and degrading battery performance. Simultaneously, during charging and discharging, the electrode material undergoes volume expansion and contraction. A specific surface area within the aforementioned range can disperse stress, reducing structural damage caused by volume changes, thereby improving the stability of the electrode material.

[0066] Furthermore, when a metal mesh is used as the electrode substrate, a higher specific surface area helps to improve the energy density of the battery. This is because, for the same volume or mass, electrode materials with a larger specific surface area can accommodate more active material, thus resulting in a higher battery capacity. In other words, with the same battery size, the battery can provide a longer driving time or a greater energy output. The relationship between battery capacity and specific surface area is shown in Equation 1:

[0067] Q = kS α Formula 1

[0068] Where Q represents the battery capacity, S represents the specific surface area of ​​the metal mesh, and k and α are constants related to factors such as battery materials, structure, and manufacturing process. For example, α is 0.5 to 1.5.

[0069] In this embodiment, preferably, the thickness of the rolled metal foil 1 is 10 nm to 1000 nm, and the specific surface area of ​​the honeycomb mesh is 0.2 m². 2 / g~50m 2 / g. Further, when the rolled metal foil 1 is copper foil, the thickness of the rolled metal foil 1 is 10nm~1000nm, and the specific surface area of ​​the honeycomb network is 0.22m². 2 / g~22.4m 2 / g; When the rolled metal foil 1 is aluminum foil, the thickness of the rolled metal foil 1 is 75nm~150nm, and the specific surface area of ​​the aluminum honeycomb mesh is 5m². 2 / g~10m 2 / g; When the rolled metal foil 1 is steel foil with a thickness of 25nm~51nm, the specific surface area of ​​the steel honeycomb mesh is 5m². 2 / g~10m 2 / g.

[0070] In any of the above embodiments, the tensile strength of the metal mesh is 30-700 MPa, and further, the tensile strength of the metal mesh is 120-350 MPa, and the elongation of the metal mesh is less than 10%. The tensile strength of the metal mesh mainly depends on the tensile strength of the rolled metal foil 1. Specifically, when the rolled metal foil 1 is copper foil, the tensile strength of the rolled metal foil 1 is 200-350 MPa, corresponding to a tensile strength level of 200-350 MPa for the metal mesh, and the elongation of the metal mesh is less than 10%; when the rolled metal foil 1 is aluminum foil, the tensile strength of the rolled metal foil 1 is 120-200 MPa, corresponding to a tensile strength level of 120-200 MPa for the metal mesh, and the elongation of the metal mesh is less than 5%; when the rolled metal foil is lithium foil, the tensile strength of the rolled metal foil 1 is 30-100 MPa, corresponding to a tensile strength level of 30-100 MPa for the metal mesh; when the rolled metal foil is steel foil, iron foil, or nickel foil, the tensile strength of the rolled metal foil 1 is 400-700 MPa, corresponding to a tensile strength level of 400-700 MPa for the metal mesh.

[0071] Thirdly, embodiments of this utility model disclose a method for preparing a metal mesh, used to prepare a metal mesh as described in any of the first or second aspects, comprising the following steps:

[0072] Fabrication of stacks: Reference Figure 3 Multiple spaced contact areas 11 are provided on the surface of a rolled metal foil 1 with a thickness of 0.01 μm to 100 μm, and the multilayer rolled metal foil 1 is arranged along a first direction (e.g., Figure 3 and Figure 4 As shown in the x-direction, adjacent rolled metal foils 1 are stacked and fixedly connected through contact area 11 to form a laminate. The fixing method can be adhesive bonding or welding, which can be selected by technicians according to actual needs.

[0073] Stretching: Reference Figure 4 As shown, for the stack along the first direction (e.g.) Figure 3 and Figure 4 The layers are stretched in the x-direction (as shown) to form a metal mesh. For example, a planar stretching machine can be used to stretch the layers along the first direction to form a metal mesh.

[0074] For example, to facilitate the demonstration of the stacked structure, refer to Figure 7 , Figure 7 It is a structural form formed by artificially stretching layers.

[0075] Specifically, the surface of the rolled metal foil 1 is provided with uniformly spaced contact areas 11, and the multilayer rolled metal foil 1 is arranged along a first direction (e.g., Figures 2-4 After stacking (as shown in the x-direction), adjacent rolled metal foils 1 are fixedly connected through contact areas 11 to form a stack. Then, along the first direction (e.g., in the x-direction), Figures 2-4 The stretching and stacking in the x-direction (as shown) creates a gap between adjacent rolled metal foils 1, which forms a mesh 10. That is, adjacent rolled metal foils 1 are stretched apart during the stretching process to form a mesh 10, which is parallel to the first direction (e.g., in the x-direction). Figures 2-4 The planar distribution is regular (as shown in the x-direction), and along the thickness direction of the metal mesh (e.g., Figure 2 and Figure 3 (Extends in the y-direction shown).

[0076] Therefore, this preparation method not only significantly improves the production efficiency of metal mesh, but also gives the metal mesh a large specific surface area, and excellent mechanical and electrical properties.

[0077] In some possible embodiments provided by this utility model, the present utility model obtains the aforementioned metal mesh by using a rolled metal foil 1 with a thickness of 0.01μm to 100μm in the preparation method of a honeycomb core. Specifically, firstly, a plurality of spaced contact areas 11 are formed by coating the surface of the rolled metal foil 1 with a thickness of 0.01μm to 100μm using a coating machine. The contact areas 11 are coated with solder or adhesive, for example. When the contact areas 11 are coated with solder, adjacent rolled metal foils 1 are welded through the contact areas 11 to form a fixed connection and a stack; when the contact areas 11 are coated with adhesive, adjacent rolled metal foils 1 are heated to cure the adhesive in the contact areas 11 to achieve a fixed connection and a stack. Subsequently, the stack is stretched along a first direction (e.g., using a planar stretching machine) Figure 3 and Figure 4 The metal mesh is stretched in the x-direction shown to form a metal mesh.

[0078] Fourthly, embodiments of this utility model disclose an electrode material, including a metal mesh as described in any of the embodiments of the first or second aspect, or a metal mesh obtained by a preparation method as described in any of the embodiments of the third aspect.

[0079] By employing the above technical solution, the electrode material, through the use of a metal mesh with a honeycomb network structure, not only significantly improves the specific surface area, ion transport efficiency, and energy density of the electrode material, but also optimizes the stability and mechanical properties of the electrode material.

[0080] Fifthly, embodiments of this utility model also disclose a battery, including the electrode material as described in the fourth aspect embodiment.

[0081] By employing the above technical solution, the ion transport efficiency of the battery is greatly improved due to the use of a metal mesh with a honeycomb network structure in the electrode material. The honeycomb network structure provides numerous active sites and efficient electrolyte permeation channels, enabling ions to rapidly insert and extract onto the electrode surface. This not only shortens the battery's charge and discharge time but also significantly increases its power density.

[0082] Secondly, the high specific surface area of ​​the metal mesh allows the electrode material to accommodate more active material within the same volume or mass, thus storing more energy. This means that, within the same battery size, the battery can provide longer driving time or greater energy output.

[0083] Furthermore, the honeycomb network structure of the metal mesh effectively buffers the volume changes of the electrode material during charging and discharging, reducing structural damage caused by stress concentration. This allows the battery to maintain stable performance over long-term use, extending its lifespan and reducing maintenance and replacement costs.

[0084] Meanwhile, the uniform structure and high mechanical strength of the metal mesh enable the electrode material to maintain good stability during battery operation, reducing safety hazards caused by mechanical damage or structural failure. Furthermore, efficient ion transport and uniform electrolyte distribution also reduce the risk of localized overheating within the battery, further improving battery safety.

[0085] It should be noted that, based on the state of the electrolyte, the batteries of this invention include solid-state batteries, semi-solid-state batteries, and liquid batteries. For example, a solid-state battery refers to a battery in which the electrolyte is solid.

[0086] The following will describe a more specific implementation method.

[0087] Example 1

[0088] Example 1: A method for preparing a metal mesh, comprising the following steps:

[0089] Fabrication of the stack: Multiple spaced contact areas 11 are formed on the surface of a 0.01 μm thick rolled metal foil 1. The multiple layers of rolled metal foil 1 are stacked along a first direction, and adjacent rolled metal foil 1 are fixedly connected through the contact areas 11 to form a stack. The rolled metal foil 1 is copper foil.

[0090] Stretching: The layers are stretched along the first direction to form a metal mesh.

[0091] In Example 1, the specific surface area of ​​the honeycomb mesh was 22.4 m². 2 / g, the thickness of the metal mesh is 5mm, the tensile strength of the metal mesh is 200~350Mpa, the thickness d1 of the hole wall of mesh 10 is 0.01μm, and the volume of mesh 10 accounts for 99.9% of the volume of the metal mesh.

[0092] Example 2

[0093] Example 2: A method for preparing a metal mesh, comprising the following steps:

[0094] Fabrication of the stack: Multiple spaced contact areas 11 are formed on the surface of a 0.075 μm thick rolled metal foil 1. The multiple layers of rolled metal foil 1 are stacked along a first direction, and adjacent rolled metal foil 1 are fixedly connected through the contact areas 11 to form a stack. The rolled metal foil 1 is aluminum foil.

[0095] Stretching: After stretching the laminate along the first direction, a metal mesh is formed, and the resulting metal mesh is as follows: Figure 8 and Figure 9 As shown.

[0096] In Example 2, the specific surface area of ​​the metal mesh was 10 m². 2 / g, the thickness of the metal mesh is 5mm, the tensile strength of the metal mesh is 120~200MPa, the thickness d1 of the hole wall of mesh 10 is 0.075μm, and the volume of mesh 10 accounts for 99.9% of the volume of the metal mesh.

[0097] To facilitate understanding of this utility model, the following parameter testing methods are explained:

[0098] Thickness testing methods (including the testing of rolled metal foil thickness and metal mesh thickness): Rolled metal foil or metal mesh of different materials are tested according to GBT22638.1-2016, GB T36146-2018, GB T5187-2021, GB T41608-2022 and GB T15077-2008 respectively to detect the corresponding thickness.

[0099] Test method for tensile strength: Tensile test shall be performed according to GB / T228-2010 Metallic materials, room temperature tensile test method, to detect and obtain tensile strength.

[0100] Elongation test method: Tensile test shall be performed according to GB / T228-2010 Metallic materials, room temperature tensile test method to detect elongation.

[0101] Test method for cross-sectional area and volume of mesh: Test according to ISO 15901-2 to detect the cross-sectional area and volume of the obtained mesh.

[0102] Specific surface area test method: The metal mesh is tested according to ISO 9277 to determine the specific surface area of ​​the metal mesh.

[0103] Although the present invention has been illustrated and described with reference to certain preferred embodiments, those skilled in the art should understand that the above description is a further detailed explanation of the present invention in conjunction with specific embodiments, and should not be construed as limiting the specific implementation of the present invention to these descriptions. Those skilled in the art can make various changes in form and detail, including some simple deductions or substitutions, without departing from the spirit and scope of the present invention.

Claims

1. A metal mesh, characterized in that, The metal mesh serves as an electrode active material or electrode substrate in the battery. The metal mesh is a honeycomb-shaped grid structure formed by stacking, fixing and connecting and stretching multiple layers of rolled metal foil with a thickness of 0.01μm to 100μm in a first direction. The mesh openings of the metal mesh are through holes, and the mesh openings are formed by the spacing between adjacent rolled metal foils through stretching.

2. A metal mesh, characterized in that, The metal mesh serves as an electrode active material or electrode substrate in the battery. The mesh openings are through holes, and the mesh openings are arranged to form a honeycomb-like grid structure. The mesh openings are formed by the spacing between adjacent rolled metal foils in a multi-layer stacked rolled metal foil. The hole walls between adjacent mesh openings are the base layer of the rolled metal foil, and the thickness of the hole walls is 0.01 μm to 100 μm.

3. A metal mesh as described in claim 1 or 2, characterized in that, The specific surface area of ​​the metal mesh is 0.1 m². 2 / g~100m 2 / g.

4. A metal mesh as described in claim 1 or 2, characterized in that, The rolled metal foil is copper foil, aluminum foil, lithium foil, steel foil, iron foil, or nickel foil.

5. A metal mesh as described in claim 4, characterized in that, When the rolled metal foil is copper foil, the tensile strength of the rolled metal foil is 200-350 MPa; when the rolled metal foil is aluminum foil, the tensile strength of the rolled metal foil is 120-200 MPa; when the rolled metal foil is steel foil, iron foil, or nickel foil, the tensile strength of the rolled metal foil is 400-700 MPa; when the rolled metal foil is lithium foil, the tensile strength of the rolled metal foil is 30-100 MPa.

6. A metal mesh as described in claim 1 or 2, characterized in that, The surface roughness (Rz) of the rolled metal foil is 0.6 to 1.5 μm.

7. A metal mesh as described in claim 1 or 2, characterized in that, The cross-sectional shape of the mesh is quadrilateral or hexagonal.

8. A metal mesh as described in claim 1 or 2, characterized in that, The wall thickness of the mesh between adjacent mesh openings is 0.01 μm to 1 μm.

9. A metal mesh as described in claim 1 or 2, characterized in that, The volume of the plurality of mesh openings accounts for 75% to 99.994% of the volume of the metal mesh.

10. A metal mesh as described in claim 1 or 2, characterized in that, The thickness of the metal mesh is 0.1 mm to 50 mm.

11. An electrode material, characterized in that, Includes the metal mesh as described in any one of claims 1 to 10.

12. A battery, characterized in that, Includes the electrode material as described in claim 11.